Tapahtuma-alan rooli Suomen taloudessa - Jyrki Ali-Yrkkö; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2021)
– In this study, we analyse the size and role of the Finnish event industry by utilising both industry- and firm-level data. Furthermore, we study the impacts of the Covid-19 crisis on companies operating in the event industry. Based on our results, the event industry accounts for 1.2% of the Finnish GDP. It should be noted that in addition to companies, the event industry consists of associations, foundations and other non-profit organisations. Depending on the definition, the Finnish event industry included in 2019 approximately 8,354-9,126 companies with 15,200-19,500 employees (full-time equivalent), which corresponds to 0.9-1.2% of the employment of all companies. The companies operating in the event industry generated EUR 800-1,200 million value added, corresponding to 0.6-0.9% of the value added of all companies. The turnover decreased between 2019 and 2020 for 70% of these companies. In every fourth of the companies, turnover decreased by at least 50%. Due to update delays of the firm-level data, these shares are probably downward biased because we were not able to take into account the role of companies that that ceased operations.
Keywords: L16; L8; L84; 330; Event industry; Event; Significance; Covid-19; Impact; Role; Definition